2017
DOI: 10.3390/geosciences7040133
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Contamination of Cattle in Artisanal and Small-Scale Gold Mining in Bombana, Southeast Sulawesi, Indonesia

Abstract: Abstract:The industrial mining sector is one of the main contributors to environmental damage and toxic metal pollution, although some contamination originates from natural geological sources. Due to their position at the top of the food chain, cattle tend to bioaccumulate mercury (Hg) in their bodies. We used analyses of cattle hair samples to investigate Hg contamination in cattle farmed within and outside of an artisanal and small-scale gold-mining area in Bombana, Southeast Sulawesi, Indonesia. We also exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…As listed in Table 3 , there were also incidents of livestock being killed by cyanide poisoning in Pesawaran. Other studies reported that mercury contamination was also present in livestock [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…As listed in Table 3 , there were also incidents of livestock being killed by cyanide poisoning in Pesawaran. Other studies reported that mercury contamination was also present in livestock [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hg enters the environment in the form of metallic Hg. The combustion of fossil fuels, burning of wastes, smelting, and mining contribute to about 80% of the aggregate, with volcanoes and forest fires accounting for the rest [ 53 ]. Many countries have designated Hg as a dangerous priority metal and thus have, through the worldwide Minamata Convention, signed an agreement to lower global anthropogenic emissions aimed at addressing various environmental and health issues related to the metal [ 54 ].…”
Section: Narrative Reviewmentioning
confidence: 99%
“…Mohammed et al [ 9 ] reported the presence of Hg in abattoir liquid waste. From another perspective, Sakakibara et al [ 53 ] aver that the Hg that remains in the terrestrial food chain could be a source of Hg pollution in animals. Hg in abattoir liquid waste can be attributed to animals' diet, including contaminated grass or other plants, drinking water, and small amounts of soil.…”
Section: Narrative Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…These sorts have varying degrees of impact on human organs such the gastrointestinal tract, the central nervous system, the immune system, the skin, the eyes, and the respiratory system. The amount of mercury released into the environment as a result of human activities, such as the generation of electricity through the processing of industrial waste, the burning of coal, the incineration of waste at homes, and the mining of mercury (along with gold and other metals), has significantly increased [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%